Presentation of Special issue: Promoting Good Health and Developing a Sustainable Environment - Halpern, G. M. (Progress in Nutrition, 2011)
Progress in Nutrition has again generously accepted to publish these abbreviated Proceedings of the 5th International Symposium on Functional Foods ‘Promoting Good Health & a Sustainable Environment’ that took place on March 10-11, 2011 at the Hong Kong Polytechnic University.This Symposium had many incarnations, and this very 5th edition even more. After 4 large programs devoted mostly to Functional Foods, we decided to follow the directive of the Government of the Hong Kong SAR that initiated a large program focused on “Good Health & a Sustainable Environment”.Since our Department of Applied Biology & Chemical Technology offers a Bachelor’s Degree (Hons.) on Food Safety & Technology, the first day of the Symposium was devoted to safety issues. But water is of major concern in Asia, China, and Hong Kong, and we decided to address water purification and environmental issues on the second day. The Poster session was very diverse and successful. Participants came from four continents and the contacts established in 2011 should reverberate on the 6th Symposium scheduled for October 25-26, 2012.The 5th International Symposium on Functional Foods was organized by Wai Yin Pang, MSc, Ailsa Yuen, BPharm, Ray Cooper, PhD and the indefatigable support of the Hong Kong Polytechnic University, with help from numerous institutions and universities.We hope that you will enjoy reading these Proceedings as much as we did attending the presentations!Hong Kong, March 2011